The effect of joint width between blocks in concrete block pavement - Mudiyono, Rachmat; Md. Nor, Hasanan; Ling, Tung Chai (2006)
Jointing sand is the main component of concrete block pavement (CBP) that promotes load transfer between blocks. Often, when sands are available from various sources, it becomes a difficult task to judge the right source of sand. This paper presents the results of an experimental program, conducted to demonstrate a quick and simple technique, for selecting the right source of jointing sand for CBP. The optimum joint width between blocks is 3 mm. For joint widths less than the optimum, the jointing sand was unable to enter between blocks. A large amount of sand remained outside the joint sand heaps on the block surface